A Microfiber Sensor for the Trace Copper Ions Detection Based on Ternary Sensitive film. Issue 22 (1st July 2022) - Chen, Jiguang; Sun, Dandan; Xu, Shaomin; Fu, Yongming; Yang, Yukun; Ma, Jie
Abstract: An optic‐fiber sensor for detecting the concentration of trace copper ions is proposed using a ternary cross‐linked sensitive film coated on the Mach–Zehnder microfiber interferometer surface. The microfiber has a huge evanescent field offering high sensitivity to the ambient refractive index. The chelation between imidazole groups in the coated thin film and copper ions changes the refractive index of the sensor surface, which is converted into macroscopic wavelength drift in the interference spectrum. The sensitivity of the sensor is up to 7.715 × 10 6  nm M −1 with the detection limit of 0.0576 ppm. This sensor can effectively avoid the effect of temperature cross‐response and has good specificity and stability. This study has instructive meanings for designing optical pollutant sensors with high stability and improved detection accuracy in a potentially multi‐characteristic environment. Abstract : A ternary cross‐linked sensitive film successfully coated on Mach–Zehnder microfiber interferometer surface is proposed with good specificity and stability. The chelating effect between imidazole groups in the coating film and copper ions change the refractive index of the sensor surface, which is converted into a macroscopic wavelength shift and the trace concentration of copper ion in water could be detected.